The Effect of Bamboo’s Root PGPR Concentration and Row Spacing on Growth and Yield of Kidney Bean (Phaseolus vulgaris) - R. Budiasih; Lia Amalia; Yuli Nurfatwa (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2018)
The experiment aims to know and learn an interaction of bamboo’s root concentration and row spacing on growth and yield of kidney bean (Phaseolus vulgaris). This experiment was carried out at Gunungmanik Village, in the sub district Tanjungsari Sumedang from May until July 2016. The altitude is about 800 meters above sea level, soil order andisol with pH 6,41 and types of rainfall is C (dampy). Design was used as Randomized Block Design (RBD) composed of two factor treatments with two replications. First factor was concentration of PGPR (Plant Growth Promoting Rhizobacteria) bamboo’s root with four level of treatment, namely is p0 = 0 ml L-1 solution, p1 = 5 ml L-1 solution, p2 = 10 ml L-1 solution, and p3 = 15 ml L-1 solution and row spacing with four level of treatments, namely is : j1 = 20 cm x 20 cm, j2 = 30 cm x 20 cm, j3 = 40 cm x 20 cm, dan j4 = 50 cm x 20 cm. The result of the experiment showed there are interaction between concentration of PGPR bamboo’s root and row spacing to plant height age 35 DAP. The result observation of growth shows the highest of plant height on giving concentration of PGPR bamboo’s root 15 ml L-1 solution accompanied row spacing 40 cm x 20 cm (p3j3) that is 74,1 cm, while on observation result shows wet weight of the seeds on giving concentration PGPR bamboo’s root 5 ml L-1 solution that is 3259,27 g and the use of row spacing 20 cm x 20 cm that is 4222,69 g. The effects bamboo’s root PGPR concentration and row spacing to plant height, number of leaves, numbers of pod per plot, numbers of seed per plot, wet weight of the seeds (pods), dry weight of the seeds (pods), wet weight of the seeds (without pods), dry weight of the seeds (without pods), and weight of 100 grains.